2019
DOI: 10.1126/sciadv.aav8575
|View full text |Cite
|
Sign up to set email alerts
|

Giant intrinsic spin Hall effect in W 3 Ta and other A15 superconductors

Abstract: The spin Hall effect (SHE) is the conversion of charge current to spin current, and nonmagnetic metals with large SHEs are extremely sought after for spintronic applications, but their rarity has stifled widespread use. Here, we predict and explain the large intrinsic SHE in β-W and the A15 family of superconductors: W3Ta, Ta3Sb, and Cr3Ir having spin Hall conductivities (SHCs) of −2250, −1400, and 1210 ℏe(S/cm), respectively. Combining concepts from topological physics with the dependence of the SHE on the sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 51 publications
5
43
1
Order By: Relevance
“…Our predicted intrinsic spin Hall conductivity for α-W (-762 (Ω-cm) −1 ) is comparable to the value (-785 (Ω-cm) −1 ) predicted by Sui et al 6 from first principles. However, our predicted intrinsic SHC for pristine β-W (-1840 (Ω-cm) −1 ) is much closer to that of Derunova et al 47 (-1900 (Ω-cm) −1 ) than the SHC (-1255 (Ω-cm) −1 ) reported by Sui et al 6 . It is unclear why there is a difference in this case.…”
Section: E Total Spin Hall Conductivitysupporting
confidence: 82%
See 2 more Smart Citations
“…Our predicted intrinsic spin Hall conductivity for α-W (-762 (Ω-cm) −1 ) is comparable to the value (-785 (Ω-cm) −1 ) predicted by Sui et al 6 from first principles. However, our predicted intrinsic SHC for pristine β-W (-1840 (Ω-cm) −1 ) is much closer to that of Derunova et al 47 (-1900 (Ω-cm) −1 ) than the SHC (-1255 (Ω-cm) −1 ) reported by Sui et al 6 . It is unclear why there is a difference in this case.…”
Section: E Total Spin Hall Conductivitysupporting
confidence: 82%
“…It is unclear why there is a difference in this case. Both previous works used a Kubo-Greenwood approach where the Bloch wave functions from plane-wave (VASP for Sui et al 6 ) or localized orbital calculations (FPLO for Derunova et al 47 ) were mapped onto a tight-binding atomic basis set. The β-W A15 crystal structure is a more open crystal structure than α-W crystal structure and this could make the mapping process to a localized basis set more challenging.…”
Section: E Total Spin Hall Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the energy efficiency of SOT‐driven magnetization switching, considerable efforts have been made to enhance the charge‐spin conversion efficiency of HM [ 6–9 ] and reduce the shunting current in the FM. [ 10,11 ] Engineering the bilayer structure [ 9,12 ] or replacing HM by novel materials with larger charge‐spin conversion efficiency and higher conductivity [ 10,13,14 ] are possible avenues to realize higher SOT efficiency.…”
Section: Figurementioning
confidence: 99%
“…The remaining real-space matrix elements are evaluated in a similar manner, by inverting Eqs. (28) and (29) and then using Eq. (35).…”
Section: Spin-current Matrix Elementsmentioning
confidence: 99%